Role of tranexamic acid to reduce blood loss and transfusion of allogeneic blood in the field of surgery - Shrestha, Indra K.; Si, Yong Yu; Tao, Jian Ping (Asian Journal of Medical Sciences, 2020)
Tranexamic acid is widely used as an antifibrinolytic drug to reduce blood loss intraoperative and postoperative time periods as well as to reduce transfusion of allogeneic blood. After releasing in the market, multidisciplinary surgeries have wide use of tranexamic acid due to its antifibrinolytic effect to reduce bleeding and transfusion of blood. In literature, there were mentioned a few adverse effects like thromboembolism, seizure, anaphylactic reaction, etc which are still unsolved questions to date. The aim of this review to minimize the blood loss from acute bleeding in different situations by updating the doses used in a different clinical scenario,since the release of tranexamic acid. It also gives an idea about appropriate doses to reduce blood loss, need for blood transfusion, minimize adverse effects and to understand the wide scope of application of TXA to date.